Forward recursion approach of electromagnetic wave propagation characteristics in a slab of inhomogeneous magnetoplasma - AL-Khateeb, A. M.; Khasawneh, M. A.; Bawa’aneh, M. S. (Advanced Electromagnetics, 2019)
Propagation characteristics of electromagnetic radiation incident on an inhomogeneous magnetoplasma slab near a good conducting metallic surface is investigated. The inhomogeneous plasma slab is divided into thin layers (sub-cells) in order to allow for treating each plasma sub-cell as a homogeneous medium. A global matrix is formed upon matching the fields at all interfaces, which allows for the analytical determination of the reflection, absorption and transmission coefficients. For matching the tangential fields at the metallic surface, an impedance (Leontovich) boundary condition has been used. Propagation characteristics are calculated numerically for a set of parameters that may be suitable for many applications including stealth plasma. Numerical results show resonant absorption peaks near the electron cyclotron frequency that increase by increasing the equilibrium plasma density. They also show absorption enhancement by increasing the plasma slab width.